Optimization of the Alpha Energy Deposited in Radioluminescence Thin Film for Alphaphotovoltaic Application - Purbandari, Dessy; Ferdiansjah, Ferdiansjah; Sujitno, Tjipto (Proceeding International Conference on Science and Engineering, 2019)
Activated zinc sulfide (ZnS) is a semiconductor material which able to emit photon in the form of visible light when expose to external energy. The capability of activated ZnS, mainly doped with silver (Ag) and copper (Cu), to convert radiation become light to make it potentially applicable as the radioluminescent thin film for alphaphotovoltaic-type nuclear battery. One of the important specifications of the radioluminescence layer that influences the fluorescence efficiency is the thickness. This work presents a study on the thickness optimization for ZnS:Ag:Cu as the radioluminescent film for alpha particles using Monte Carlo model. Simulation to study alpha particles’ energy deposited by using Stopping and Range of Ions in Matter/TRansport of Ions in Matter (SRIM/TRIM) code. The model examined the transport of 5.485 MeV alpha particles emitted by to determine the best thickness based on energy deposition depth. Based on TRIM module simulation, the optimal thickness for radioluminescence film is approximately 19-22 µm. Most energy from 5.485 MeV alpha particles is deposited in 18.92 µm depth activated zinc sulfide. The results from SRIM/TRIM model then compare with analytical calculation using Bragg-Kleman rule. The alpha particles stop at 22 µm from the SRIM/TRIM simulation while using Bragg-Kleman formula the alpha particles stop at 23.51 µm.